2009
DOI: 10.1007/s12134-009-0104-1
|View full text |Cite
|
Sign up to set email alerts
|

Are Immigrants Socially Isolated? An Assessment of Neighbors and Neighboring in Canadian Cities

Abstract: Recently, the media have expressed concern about the apparent concentration and social isolation of immigrants in central and inner suburban neighborhoods in large Canadian cities. This paper compares and contrasts the frequency and nature of neighborhood-based social contacts among three cohorts of immigrants distinguished by their period of arrival in Canada and Canadian-born individuals. We begin by outlining the family, friend, and acquaintance relationships that immigrants build and argue that their netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
2
11
0
2
Order By: Relevance
“…The likelihood of Blacks facing higher hate crime victimization is consistent with other studies (see e.g., Bania, Janhevich, & Hastings, 2008;Ray & Preston, 2009). This confirms the hypothesis that among the visible minority groups, the likelihood of hate crime victimization among Blacks will be higher compare to nonvisible minority groups.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The likelihood of Blacks facing higher hate crime victimization is consistent with other studies (see e.g., Bania, Janhevich, & Hastings, 2008;Ray & Preston, 2009). This confirms the hypothesis that among the visible minority groups, the likelihood of hate crime victimization among Blacks will be higher compare to nonvisible minority groups.…”
Section: Discussionsupporting
confidence: 90%
“…Since all the odds for fear of hate crime are significant, it gives credence to the proposition made earlier that hate crime is more of a race issue than ones' socioeconomic status. Similarly, Ray and Preston (2009) and Janhevich, Bania, and Hastings (2008), found in their study that those who have been victims of hate crime are four times more likely to be worried about hate-crime victimization.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Specifically, a sense of trust in others and especially in neighbors reduces the odds of reporting racial discomfort and discrimination. While numerous studies have demonstrated that social ties with neighbors are usually weak or very casual (Ray & Preston 2009), these informal types of socializing may be very important in constructing a sense of belonging, especially among newcomers to Canada.…”
Section: Discussionmentioning
confidence: 99%
“…Certains font appel aux réseaux sociaux (Arcand et al 2009 ;Piché et al 2002). En effet, ces réseaux constituent souvent des mécanismes de transmission de l'information sur le milieu du travail pour les immigrants (La Grenade 2009) et peuvent faciliter leur accès aux ressources et aux opportunités d'emploi (Castles et Miller 2003 ;Ray et Preston 2009 ;Ryan et al 2008 ;Statistique Canada 2003). D'autre part, certains employeurs cherchent d'abord leur maind'oeuvre dans leur entourage.…”
Section: Intégration En Emploi Des Immigrants Et Apport Des Services unclassified